The Economic Outcomes of an Ethnic Minority: the Role of Barriers - Nitsa (Kaliner) Kasir; Eran Yashiv (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2020)
The Arab population in Israel constitutes an ethnic minority, at around 20% of the population. The economy of this minority is characterized by inferior outcomes relative to the Jewish majority by all indicators, including employment, wages, occupational status, social welfare, education, and housing. This paper reviews key data facts and presents a model of barriers to integration facing Arabs in Israel, taking it to the data. The empirical analysis, based on a general equilibrium model of occupational choice with optimizing agents and barriers, points to an increase over time in barriers to the acquisition of human capital in highly skilled occupations, and, concurrently, a reduction in labor market barriers in all occupations. The analysis offers insights relevant to other developed economies with large ethnic minorities.
Keywords: 330